Psychological flexibility as a predictor of professional quality of life in newly qualified psychological therapy practitioners - Garner, Emma Victoria (2022)
The professional quality of life of psychological therapy practitioners can be conceptualised within a compassion satisfaction and compassion fatigue framework. Compassion fatigue is purportedly separated into two components of burnout and secondary traumatic stress. Compassion fatigue can have detrimental impacts on therapy practitioners, organisations and patient care, whereas compassion satisfaction is associated with positive outcomes. Consequently, there is a need to explore factors that mitigate compassion fatigue and promote compassion satisfaction. This is particularly important for newly qualified psychological therapists who are reportedly at risk of compassion fatigue during the transition from pre- to post-qualified practice.